PHYSICO CHEMICAL ANALYSIS AND ANTI MICROBIAL ACTIVITY OF A SIDDHA HERBO MINERAL DRUG SILASATHU PAAVANAI - S. SUDHA REVATHY,; M.MURUGESAN, (International Journal of Pharma and Bio Sciences, 2013)
Indian systems of medicine are Siddha, Ayurveda and Unani. Among them, Siddha system of medicine is being practiced in southern parts in India. Siddha has its strong foundation of science laid by siddhars and other sages who aimed at attaining salvation and hence formulated medicines for a longer and healtier life span. Among the 4448 diseases mentioned by them, Kalladaippu (Urolithiasis) is one of the reasons for obstruction in the urinary system and hence producing low urinary output. Many medicines have been prescribed for this disease and Silasathu paavanai is one among them. The present study aims to analyze drug physico chemically and to explore its anti microbial activity. The drug Silasathu paavanai contains essential elements which are considered to be stone inhibitors and the aqueous extract has good anti microbial activity against E.coli which is the commonest urinary tract infection among patients with urolithiasis.